2007
DOI: 10.1038/nm1562
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus monkey TRIM5α restricts HIV-1 production through rapid degradation of viral Gag polyproteins

Abstract: Mammalian cells have developed diverse strategies to restrict retroviral infection. Retroviruses have therefore evolved to counteract such restriction factors, in order to colonize their hosts. Tripartite motif-containing 5 isoform-alpha (TRIM5alpha) protein from rhesus monkey (TRIM5alpharh) restricts human immunodeficiency virus type 1 (HIV-1) infection at a postentry, preintegration stage in the viral life cycle, by recognizing the incoming capsid and promoting its premature disassembly. TRIM5alpha comprises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
110
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 30 publications
3
110
1
Order By: Relevance
“…In addition to their effects on early postentry events, both overexpression of rhesus TRIM5␣ and overexpression of human TRIM5␣ have been reported to specifically inhibit the late-phase production of infectious HIV-1 strains (35,36,50,51), and some (35,51), but not all (50), of these studies have found that inhibiting TRIM5 expression by using siRNA constructs targeting sequences common to all TRIM5 isoforms improves HIV-1 production in cells expressing physiological levels of rhesus or human TRIM5. In this context, Sakuma et al (36) reported that a truncated version of rhesus TRIM5 lacking the SPRY domain retained the ability to inhibit HIV-1 production.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their effects on early postentry events, both overexpression of rhesus TRIM5␣ and overexpression of human TRIM5␣ have been reported to specifically inhibit the late-phase production of infectious HIV-1 strains (35,36,50,51), and some (35,51), but not all (50), of these studies have found that inhibiting TRIM5 expression by using siRNA constructs targeting sequences common to all TRIM5 isoforms improves HIV-1 production in cells expressing physiological levels of rhesus or human TRIM5. In this context, Sakuma et al (36) reported that a truncated version of rhesus TRIM5 lacking the SPRY domain retained the ability to inhibit HIV-1 production.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to participate in numerous distinct processes, including roles in development, both normal and tumorous, asymmetric cell divisions and viral response (Arama et al, 2000;Horn et al, 2004;Bello et al, 2006;Betschinger et al, 2006;Lee et al, 2006;Sakuma et al, 2007) and see Table 2 in Meroni and Diez-Roux (2005), to name but a few. This protein superfamily is characterized by the presence of multiple protein-protein interaction domains, from which it has derived its name, that is, RING, B-box, and coiled-coil domains (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The coiled-coil domain of TRIM5␣ contributes to protein oligomerization and efficient capsid binding and post-entry restriction (10,11). Disruption of the TRIM5␣rh RING domain decreases, but does not eliminate, the restriction of HIV-1 infection (8,12). Although polyubiquitination and rapid degradation of TRIM5␣ depend upon intact RING and B-box 2 domains (13), rapid turnover of TRIM5␣ is not required for its post-entry restriction activity, and proteasome inhibitors cannot prevent the post-entry restriction (9,14).…”
mentioning
confidence: 99%
“…In addition to this well characterized post-entry restriction activity, TRIM5␣rh has another "late restriction" activity to affect the production phase of the HIV-1 life cycle (12,18,19). Richardson et al (19) have demonstrated that cellassociated HIV-1 transmission in human cells is blocked only when both donor and recipient cells express TRIM5␣rh.…”
mentioning
confidence: 99%
See 1 more Smart Citation